Clinical presentations of diabetes in children attending the paediatric ward in the medical institute: a cross sectional study - Vyas, Dilipkumar Bhikhalal; Thacker, Vinit (International Journal of Advances in Medicine, 2018)
Background: By 2025, India due to its immense population size and high diabetes prevalence will contribute about 57 million diabetics. Hence the aim of the present study was clinical presentations of diabetes in children attending the paediatric ward in the medical institute. Methods: Total of 50 cases were included in the study. All the children who were less than age of 18years and also diagnosed with diabetes that is fasting blood sugar >126mg/dl or random blood sugar level > 200 mg/dl were included in the study. A detailed clinical examination of the child was carried out with detailed anthropometric measurements. Metabolic profile was done by investigating for the following. Fasting blood sugar, post prandial blood sugar, glycoslated haemoglobin. Results: The various ranges of fasting blood sugar were as follows: 25% were in the range of 130-200mg/dl, 35% in 200-300 mg/dl, 25% in 300-400mg/dl and 15% had more than 400 mg/dl fasting blood sugar levels. The various ranges of post prandial blood sugar were as follows: 16% were in the range of 200 - 300mg/dl, 40% in 300-400mg/dl, 44% had more than 400 mg/dl post prandial blood sugar levels. In the present study lipid profile of all the children was analysed by their serum cholesterol and triglycerides. Conclusions: A total of 50 diabetic children of age less than 18 years attending medical Hospital were studied using a predesigned and pretested proforma. Information was collected on socio-demographic, dietary intake, treatment and compliance history. Detailed clinical examination done and anthropometric measurements were taken. Metabolic profile was done by investigating for blood sugar levels, glycoslated haemoglobin and lipid profile. In the present study 46% had onset of diabetes mellitus at 15 to 18 years age group with male to female ratio of 1.26:1.